Antibacterial properties of synthetic peptides and schiff base compounds against different types of clinical bacteria / Chow Wei Chon - Chow, Wei Chon (2013)
The emergence of multiple drug-resistant nosocomial pathogens affects the efficacy of chemotherapeutic treatment of infectious diseases in patients. Therefore, continuous development of new synthetic antibacterial compounds such as the synthetic peptides and Schiff base complexes to complement the current antibiotic treatment is essential. The in-vitro antibacterial activities of six synthetic cationic peptides and twenty-nine synthetic Schiff base complexes towards selected sixteen clinical strains of multiple drug-resistant methicillin-resistant Staphylococcus aureus (MRSA), Acinetobacter baumannii (AC), Klebsiella pneumoniae (KB) and Pseudomonas aeruginosa (PA) were investigated in this study. Evaluation of the antibacterial activities were determined through disk diffusion testing, broth micro-dilution assay for minimum inhibitory concentration (MIC) determination, cell inactivation assay and bacterial killing rate (time-kill) assay. Some of the Schiff base ligands were bound to various metals including nickel (Ni), cobalt (Co), zinc (Zn), cadmium (Cd) and copper (Cu). Among the twenty-nine synthetic Schiff base complexes screened in the disk diffusion test, the complex containing cadmium, LMA Cd-N3, was shown to be more effective as it inhibited the growth of six randomly selected bacterial strains (KB88, KB198, MRSA080925, MRSA08071, AC06127, AC08121), resulting in zones of inhibition that were comparable to the antibiotics (polymyxin B and vancomycin) used. Results from the time-kill assay showed that the LMA Cd-N3 complex achieved complete killing of bacterial cells after exposure to the complex for 4 hours (1X MIC at 625.0 ppm), 8 hours (1X MIC at 156.3 ppm) and 12 hours (2X MIC at 625.0 ppm) for MRSA, AC and KB, respectively. On the other hand, complete killing was observed when similar strains of KB and AC were exposed to 0.5X MIC of polymyxin B (1.0 ppm) for 2 hours, while MRSA strain required 12 hours of exposure to 0.5X MIC of vancomycin (2.0 ppm). Interestingly, KB had shown regrowth of cells within 4 hours to 24 hours of exposure to polymyxin B at 0.5X MIC, indicating that polymyxin B had lost its antibiotic effect after 4 hours of exposure. Apart from having poor antibacterial activity against all bacterial strains tested in the study, some of the cationic peptides were also shown to induce growth of bacterial cells at the range of concentration from 25.0 ppm to 375.0 ppm. However, the growth of P. aeruginosa strains was not affected by the cationic peptides and Schiff base complexes where no inhibition zones were observed for the strains in the disk diffusion test. Results obtained from the assays in the study showed that both of the synthetic Schiff base complexes and cationic peptides exhibited antibacterial activity against Gram-positive and Gram-negative bacteria. Schiff base cadmium complex showed comparable results to commercial antibiotics used against bacterial strains of MRSA, A. baumannii and K. pneumoniae, whereas cationic peptides (RM) exerted slight antibacterial activities towards MRSA strains. The findings implied that the cadmium-containing Schiff base complex represents a good candidate for future research in the development of novel antibacterial compounds for treatment of diseases caused by MRSA, A. baumannii and K. pneumoniae.